(untitled) (Journal of Partial Differential Equations, 2020)
This paper regards the existence of entropy waves for a model example of nonstrictly hyperbolic system which degenerates on a sonic line. This construction is an important tool to approach the convergence of the vanishing viscosity and of other similar approximations to the weak solutions of the hyperbolic systems, via the compensated compactness techniques.